Beyond the Natural Order: Exploring English Language Acquisition in a Young Learner within Diverse Linguistic Contexts - Purnama NF Lumban Batu (Journal of Innovation in Educational and Cultural Research, 2024)
Early childhood is a critical period for language acquisition, where exposure to linguistic input and interaction plays a significant role in shaping language development. Understanding how children acquire a second language within diverse linguistic environments can provide valuable insights into the mechanisms of language learning. This study explores English language acquisition in a six-year-old child within the Natural Order Hypothesis (NOH) context. Using a case study methodology, the researcher analyzed the child's English usage through videos and interviews in a Batak-speaking environment. The goal is to determine if the child's language development followed the grammatical sequence suggested by the NOH while accounting for cognitive and sociolinguistic influences. The findings show a blend of expected NOH patterns and deviations due to the child's specific linguistic environment, media exposure, and family support. These findings emphasize the importance of input and interaction in second language acquisition (SLA), highlighting the adaptability of language learning to individual contexts. The study contributes to SLA research by demonstrating how theoretical models like the NOH intersect with the diverse experiences of learners, advocating for a holistic approach to understanding language acquisition. This research encourages further investigation into the various factors influencing language learning trajectories in young children.